The role of rural tourism in the sustainable development of local hromadas (Economics and region, 2022)
Strengthening of environmental standards of agricultural management, environmentally oriented modernization of industrial enterprises, including the traditionally dirtiest ones, modernization of transport allow to improve the quality of environmental management. Considering the transition to the paradigm of sustainable development in all spheres of social life, especially in tourism, the study of the potential for the development of rural green tourism is particularly relevant, especially under the conditions of the need to support agriculture. Approaches to state and legal regulation of rural tourism are considered on the example of leading European countries and Ukraine. Characteristics of rural tourism as a separate field of tourist activity are identified. It is shown that rural tourism is an important tool for achieving the goals of sustainable development, and its development requires simplification of bureaucratic procedures and harmonization of European and national legislation. On the example of Petrykivka municipality of Dniprovsky district ( Dnipropetrovsk Оblast) the expediency of creating a single network of green farms, connecting them with cycling, horseback riding and hiking trails, and further organizing a cluster of rural and ethnographic tourism for promotion of tourist products under a single brand of the local hromada is considered. The importance of cluster development of tourism enterprises in Dnipropetrovsk Oblast and Petrykivka hromada is based on the need to create more flexible structures capable of satisfying the growing demand for quality and environmentally friendly services. In recent years, small and medium-sized enterprises in the field of tourism have been among the leaders of growth in terms of services and goods provided in the region. At the same time, these green tourism enterprises have not only significant tourism potential, but also experience in cooperation and interaction.
Keywords: rural tourism; recreation; EU experience; local hromada; cluster; regulation; sustainable development